Quo Vadis Penelitian Hukum: Sebuah Jalan Meluruskan Miskonsepsi Kecenderungan Arah Penelitian Hukum - Muammar, Muammar; Taufik, Iqbal (Universitas Semarang, 2024)
This paper aims to analyze and correct misconceptions about the tendency towards legal research that is prevalent in our midst, especially legal research carried out by students who will complete their studies. The approach methods used in this paper are conceptual approach, analytical approach, and theoretical approach. Legal research so far has often been interpreted similarly to social research (identical). To overcome such an understanding, the science of law must be restored to its original identity. This effort can be made by making introductory courses in legal science, legal research methods, and legal philosophy as courses as the main